2008
DOI: 10.5897/ajb08.144
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of antibacterial activity and acute toxicity of the hydroethanolic extract of Stachytarpheta angustifolia (Mill) Vahl.

Abstract: The aim of this study was to evaluate antibacterial activity, acute toxicity in mice and phytochemical profiles of hydroethanolic extract of Stachytarpheta angustifolia plant. The plant S. angustifolia has attracted the attention of the researchers because of its use as an anti-infection agent. The aqueous ethanol (80%) extract of the powdered dried whole plant was obtained by maceration. The bacteria organisms tested include Shigella dysentriae (ATCC 32412), Salmonella typhi (ATCC 213415), and the following c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 11 publications
1
11
1
Order By: Relevance
“…The result of similar study by Enwuru et al (2011) showed relatively low resistance to ceftazidime, Ofloxacin, gentamycin, nitrofurantoin and Nalidixic acid by E. coli in the community, when compared with the pattern from the hospital. The indication may imply that these drugs have not been grossly misused in the vicinity studied.…”
Section: Discussionmentioning
confidence: 86%
“…The result of similar study by Enwuru et al (2011) showed relatively low resistance to ceftazidime, Ofloxacin, gentamycin, nitrofurantoin and Nalidixic acid by E. coli in the community, when compared with the pattern from the hospital. The indication may imply that these drugs have not been grossly misused in the vicinity studied.…”
Section: Discussionmentioning
confidence: 86%
“…This could be explained by the presence of potent anti-bacterial constituents in high concentrations in the extract. Moreover, the specific mode of action of active chemical constituent against microorganisms is attributed to their chemical composition and morphology [31] . The extract was also active on K. pneumonia rather than E. coli, which indicates a higher concentration of the extract is required to inhibit the growth of E. coli.…”
Section: Discussionmentioning
confidence: 99%
“…It is possible that the apparent ineffectiveness of N. sativa organic extracts was largely due to this permeability barrier. On the other hand, Gram-positive bacteria are only composed of peptidoglycan cell wall and so are more susceptible to anti-microbial agents [17,31] . Although petroleum ether extract was a crude one, it proved superior over the standard antibiotic, chloramphenicol, when testing against S. aureus, S. epidermidis and B. subtilis.…”
Section: Discussionmentioning
confidence: 99%
“…In Nepal, Bora et al [11] also reported that Klebsiella pneumoniae from clinical isolates expressed MBLs. In another related study, Enwuru et al [12] in Lagos, Nigeria also reported that Klebsiella species from hospital environments expressed MBL phenotypically, and that these organisms are resistant to some commonly available antibiotics. The emergence and spread of MBL-producing Klebsiella species in the community as reported in this study may portend public health issues if these organisms are transmitted to humans via the food chain.…”
Section: Discussionmentioning
confidence: 93%